Luteolin Binds Streptolysin O Toxin and Inhibits Its Hemolytic Effects and Cytotoxicity - Guo, Tingting; Liu, Peng; Wang, Zeyu; Zheng, Yuling; Huang, Wenhua; Kong, Decong; Ding, Lizhong; Lv, Qingyu; Wang, Zhongtian; Jiang, Hua; Jiang, Yongqiang; Sun, Liping (Frontiers in Pharmacology, 2022)
Group A streptococcus (GAS, Streptococcus pyogenes) is a common pathogen that can cause a variety of human diseases. Streptolysin O (SLO) is an exotoxin produced by GAS. It is a pore-forming toxin (PFT) that exhibits high in vivo toxicity. SLO enables GAS to evade phagocytosis and clearance by neutrophils, induces eukaryotic cell lysis, and activates inflammatory bodies. Luteolin is a natural compound that is produced by a wide range of plant species, and recent studies have shown that luteolin can inhibit the growth and alter the morphological of GAS. Here, we reported that luteolin can weaken the cytotoxicity and hemolytic activity of SLO in vitro. Briefly, luteolin binded SLO with high affinity, inhibited its dissolution of erythrocytes, affected its conformational stability, inhibited the formation of oligomers. To further verify luteolin protective effect, we used an in vitro SLO-induced human laryngeal carcinoma epithelial type-2 cells (HEp-2) model. Notably, our results showed luteolin protected HEp-2 cells from SLO induced cytotoxicity and changed in cell membrane permeability. In addition, we explored the role of luteolin in protecting mice from Streptococcus pyogenes-mediated injury using an aerosolized lung delivery model, and our results indicate that luteolin increases murine survival rate following inoculation with a lethal dose of Streptococcus pyogenes, and that survival was also associated with decreased pathological damage to lung tissue. Our results suggest that luteolin may be a novel drug candidate for the treatment of Streptococcus pyogenes infection.